Vagus Nerve Stimulation (VNS) and Other Augmentation Strategies for Therapy-Resistant Depression (TRD): Review of the Evidence and Clinical Advice for Use - Müller, Helge H. O.; Moeller, Sebastian; Lücke, Caroline; Lam, Alexandra P.; Braun, Niclas; Philipsen, Alexandra (Frontiers in Neuroscience, 2018)
In addition to electroconvulsive therapy (ECT) and repetitive transcranial magnetic stimulation (rTMS), vagus nerve stimulation (VNS) is one of the approved neurostimulation tools for treatment of major depression. VNS is particularly used in therapy-resistant depression (TRD) and exhibits antidepressive and augmentative effects. In long-term treatment, up to two-thirds of patients respond. This mini-review provides a comprehensive overview of augmentation pharmacotherapy and neurostimulation-based treatment strategies, with a special focus on VNS in TRD, and provides practical clinical advice for how to select TRD patients for add-on neurostimulation treatment strategies.